Radiotherapy Management of Nasopharyngeal Carcinoma Patient in General Hospital Haji Adam Malik Medan: A Case Report (TALENTA PUBLISHER, 2021)
Introduction: Nasopharyngeal carcinoma (NPC) is a head and neck malignancy with a high incidence especially in Asian region. NPC has highly prevalence in head and neck cancer with most of the type is squamous cell type with three different histologic subtypes, namely squamous cell carcinoma, nonkeratinizing carcinoma, and undifferentiated carcinoma. Principle of management NPC is radiotherapy because of this kind of carcinoma highly radiosensitive and is the mainstay of treatment for all stages. Case report: A 33-year-old woman came to the ENT-Head and Neck Surgery Outpatient clinic of General Hospital Haji Adam Malik Medan on March, 2021. The patient was diagnosed with Nasopharynx carcinoma, with complaints of nose bleeds and, nasal congestion. History of consuming salted fish was found. History of cooking food with flavoring was found. The patient then performed a non-contrast-enhanced nasopharyngeal MSCT scan on February 17th, 2021 with the result: Left nasopharyngeal mass that extends to the left torus tobarius, left rossenmuller fossa crossing to the right nasopharyngeal midline (T1N0M0). The histopathological results were carried out at the Vina Estetika Hospital: Keratinizing Squamous Cell Carcinoma. The patient then performed a contrast-enhanced nasopharyngeal MSCT scan on March 3rd 2021 with the result: a left-sided nasopharyngeal mass with a rosenmuller fossa and an obliterated Tobarius torus was seen. Nasopharyngeal mass (T1N0M0). The patient was given 70 gy of Radiotherapy on March 18th 2021. After radiation 35 times on May 18th 2021, the patient was evaluated on the next 8 weeks. Conclusion: Using radiotherapy alone in this patient is the best therapy for this patient. Beside that, early diagnosis in NPC was giving better result of this management